Structural and in silico studies of 2-pyridyl-decorated 2-amino-1,3,5-triazine with a potency against SARS-CoV-2 proteins - Safin, Damir A. (Comptes Rendus. Chimie, 2024)
Computational studies of 2-amino-4,6-bis(2-pyridyl)-1,3,5-triazine (NH2Py2T), which is of interest both as a ligand for coordination chemistry and as a precursor for further functionalization due to the presence of the NH2 functionality, are reported. Three isomeric structures were considered. Descriptors and potential corrosion inhibition properties for a series of metals used in implants were examined by DFT calculations. ADMET properties were estimated using a set of online tools. Potential inhibition properties toward a number of SARS-CoV-2 proteins were investigated using molecular docking, which showed the best binding score with Nsp3-MES. Stability of complexes of NH2Py2T with the considered proteins was also studied using molecular dynamics simulations, which showed that complex with Mpro is the most stable, while complex with PLpro is unstable.